(untitled) (Research, Society and Development, 2022)
The objective of this work was to describe morpho-anatomically the fruits, seeds and post-seminal development of okra (Abelmoschus sculentus (L.) Moench - cv. "Santa Cruz 47"). The fruits and seeds were characterized by shape, color, texture, type, consistency, dehiscence and dimensions. For the anatomy of the seeds, optical microscopy and scanning electron microscopy were used. According to the results, okra fruits are of the capsule type rimosa, dry, hairy, dehiscent, angular, pentacarpelar, pentalocular, pluriovular, green to dark gray color, with tapering towards the apex. The seeds are of a rounded form, albuminous, with traces of the calaza and funiculus, of gray to black color, measuring 4.91 mm and 4.36 mm in length and width, respectively. The tegument is slightly rough and formed by two layers of sclerenchymatic cells and arranged in palisade. The endosperm is white, starchy and formed by loose parenchyma cells. The embryo is plicated and the cotyledons are leafy and white in color. The embryonic axis is straight, differentiated in plumule and hypocotyl-radicular axis and covered by cotyledons of white coloration.